INTEREST OF USING E-COMMERCE CHANNELS BASED ON SOCIAL MEDIA TO IMPROVE THE QUALITY OF REGIONAL SUPERIOR PRODUCT MARKETING ON FEMALE GROUP OF CRAFTSMEN FROM SANITAIR KLASEMAN MALANG CITY - Ayu Febriyanti Puspitasari; Rizka Miladiah Ervianty; Phima Ruthia Dwikesumasari; Ida Setya Dwijayanti (Darmabakti Cendekia: Journal of Community Service and Engagements, 2019)
Background: Industrial centers (UKM) in Malang are scattered throughout the city. According to data from the Malang Cooperative and UMKM Office, only 30% have gone online from the 70,000 UMKM currently available. This is an opportunity for young people to be able to help UMKM to go online. The main obstacles experienced by UMKM are financing problems, technology and product innovation, market research and inefficiencies. Purpose: To solve the problems of MSMEs in Malang City, especially in the field of technology and product innovation for women groups, UKM Craftsmen Sanitair Klaseman Malang. Method: Training on making e-commerce based marketing channels and social media which includes training on making e-commerce channels through social media and the internet. Results: The UKM of sanitation products in Malang were mostly dominated by 50% flower pots and 25% carvings. The use of social media for UKM partners had an impact on increasing orders from consumers through social media. The types of social media used was Whatsapp (100%), Instagram (55%), and Facebook (87.5%). Communication of sellers and buyers was effective and efficient through media chat messenger. Means of direct contact between sellers and buyers reached 87.5% through social media. Conclusion: Partners got increased orders from consumers after using social media. They could also grow their business bigger because they could have transaction directly with bank transfer payment method.